Luxembourg: harnessing skills for more inclusive growth - Stráský, Jan (OECD Economics Department Working Papers, 2017)
Digitalisation, automation and future technological changes are changing the world of work, affecting the skills needed to perform them. The future of jobs will not look like the present situation: increasingly, workers will have to adapt to fast technological change, accept more mobility during their career, and regularly upgrade their skills to remain employable. Luxembourg's workforce is highly skilled, reflecting the concentration in the country of sophisticated firms in the financial sector and other top-end international services. However, some middle- skilled routine jobs - especially back office, custodian and legal services in the financial sector - may disappear as a result of automation. Workers with strong and adaptable skills will be well prepared to thrive in this new environment. While many individuals working in Luxembourg already possess such characteristics, many others do not, resulting in a relatively high level of skills mismatch.